The Effectiveness of Social Media Usage within Social Movement to Reject the Reclamation of the Jakarta Bay, Indonesia - Anam, Khairil; M Kolopaking, Lala; A Kinseng, Rilus (Sodality: Jurnal Sosiologi Pedesaan, 2020)
Presidental Degree No. 95 of 1995 in the era of President Soeharto was a fundamental basis in reclamation planning. The reason for the reclamation is to develop the Pantura area as an economic area and land expansion in Jakarta. However, this policy was opposed by many groups, one of which was the Ministry of the Environment by issuing the results of the 2003 Environmental Impact Study which stated that reclamation was not feasible to be continued. In addition, the reclamation plan had the potential to harm 17,000 fishermen who lived in the Jakarta bay reclamation development area; they felt the impact socially, economically and environmentally. The purpose of this study is to analyze the effectiveness of the reclamation rejection movement in the digital age. The paradigm of this research is constructivism, with qualitative and quantitative method approaches. Data retrieval on social media was carried out in Python 3 and Drone Emprit Academic to obtain SNA results and conversation trends and the distribution of issue locations on Twitter. This research was conducted in the Kaliadem and Kalibaru Fishermen Village, North Jakarta, involving 50 respondents and 5 informants. The result showed that social media has an effective role in encouraging the sensitivity of public attitudes in the movement. This is evidenced by the expansion of the message to reject reclamation in various regions, and it can encourage policy changes. Keywords: digital activism, fisherfolkfisher folk movement, reclamation, social media, social movement